MODEL PROPORSI TABARRU' DAN UJRAH PADA BISNIS ASURANSI UMUM SYARIAH DI INDONESIA - Puspitasari, Novi (Jurnal Akuntansi dan Keuangan Indonesia, 2012)
This study aimed to explore the fund separation concept of the financial management on the Islamic general insurance companies, in particular what factors effected on the determination of the proportion tabarru’–ujrah and its relationship to financial performance. This study used a qualitative method in case study type. This research used general insurance companies with full Islamic system as research object. The results showed that the determination of the proportion tabarru‘-ujrah influenced by risk factors, the financial aspects of the company, and retakaful activities. Determination of the proportion of tabarru’-ujrah effects on the company’s financial performance (risk based capital / solvency). This study can build a model of determination of the proportion of tabarru’-ujrah, so that the model can be used as a basic model for further research.